LEVEL OF CRABLET PRODUCTION IN MANGROVE CRAB Scylla paramamosain WITH FEEDING ENRICHMENT USING HUFA AND VITAMIN C ON LARVAE STAGES - . Gunarto; . Herlinah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The objective of the research was to determine the best enrichment of rotifer and the naupli of Artemia as feed  for mud crab, S. paramamosain larvae,  also to know their increasing of the DHA/EPA ratio and vitamin C content. Four treatments were tested, namely : A) Mud crab larvae every two days were given  rotifer and naupli of Artemia enriched with HUFA and vitamin C also added RICA-1 probiotic at 2 mg/L,  B) Mud crab larvae every two days were given rotifer and naupli of Artemia enriched with HUFA  and vitamin C,  C).  Mud crab larvae every two days were given rotifer and naupli of Artemia enriched with vitamin C, and D).  Mud crab larvae every three days were given rotifer and naupli of Artemia enriched with vitamin C. Result showed that the crablet production from the highest to the lowest was as follows: treatment A (177.5+17.6 ind./tank), treatment B (160+14.1 ind./tank) (A and B showed no significant different results (P>0.05)), treatment C (136+5.6 ind./tank), and treatment D (106+8,5 ind./tank) (C and D results indicated a significantly different (P<0.05) with treatment A).   Higher level of DHA/EPA ratio of 69.23% was found on rotifer enriched with HUFA, while on naupliofArtemia only 28,72%. Higher level content of vitamin C was 50.56% in rotifer enriched with vitamin C, while in naupli of Artemia was only increase to 35.56%.Keywords:  Scylla paramamosain larvae, enrichment,  HUFA, vitamin C, crablet